2019
DOI: 10.15388/omee.2019.10.10
|View full text |Cite
|
Sign up to set email alerts
|

It is Domestic, it Must Be Healthy: How Health Consciousness and Consumer Ethnocentrism Shape Healthiness Perception and Purchase Intentions of Domestic Food

Abstract: Consumer ethnocentrism (CET), healthiness perception and health consciousness have been extensively researched in regard to consumer food choices. Literature on domestic food choices provides evidence that CET positively affects consumer preferences toward domestic food. However, the effect of health consciousness on domestic food choices has not yet received attention. Our online study (N=227, convenience sample from Lithuanian population) closes this gap by showing that health consciousness is an important i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 67 publications
0
3
0
1
Order By: Relevance
“…In this regard, Tuk and colleagues (Tuk et al 2015) have shown that self-control instigates positive spillover effects from the domain in which it is exercised into other domains in which it was not initially exercised, and state that, for example, increased attentional or emotional control can reduce unhealthy food consumption. Consumer ethnocentrism, in this sense, should therefore not only lead consumers to perceive national food as higher quality, but also incite them to perceive it as healthier (Uzdavinyte et al 2019;Dogi 2015).…”
Section: Consumer Ethnocentrism Literaturementioning
confidence: 99%
“…In this regard, Tuk and colleagues (Tuk et al 2015) have shown that self-control instigates positive spillover effects from the domain in which it is exercised into other domains in which it was not initially exercised, and state that, for example, increased attentional or emotional control can reduce unhealthy food consumption. Consumer ethnocentrism, in this sense, should therefore not only lead consumers to perceive national food as higher quality, but also incite them to perceive it as healthier (Uzdavinyte et al 2019;Dogi 2015).…”
Section: Consumer Ethnocentrism Literaturementioning
confidence: 99%
“…There is also a difference in purchasing behavior seen across levels of a country's economic development, as people have different economic abilities to buy a product (Li et al 2020). There have been studies examining the correlation between health, environmental and ethical concerns and purchase behavior in both high-income (Uzdavinyte et al 2019;Schill et al 2019) and low-and middle-income countries (Tong and Kang 2019;Malik et al 2019), with mixed findings. Studies suggest a positive association between health concern and purchase behavior in some developing countries, such as Turkey (Yazar and Burucuoglu 2019), but no such association in others, such as Thailand (Sriwaranun et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A continuación, se mostrará toda la metodología realizada en el proceso de búsqueda y selección de artículos en las bases de datos, plasmadas en las siguientes tablas y esquemas. 2013 México Proquest [10] 2013 España Scielo [11] 2013 Brasil Scopus [12] 2013 Italia Scopus [13] 2013 Países Bajos Scopus [14] 2014 España Redalyc [15] 2014 Malaysia Scopus [16] 2015 Perú Proquest [17] 2015 Chile Scielo [18] 2015 Estados Unidos Scopus [19] 2016 Colombia Dialnet [20] 2016 Brasil Redalyc [21] 2016 Turquía Scopus [22] 2017 Chipre Scopus [23] 2017 Polonia Scopus [24] 2018 España Dialnet [25] 2018 España Ebsco [26] 2018 España Ebsco [27] 2018 México Redalyc [28] 2018 México Redalyc [29] 2019 España Dialnet [30] 2019 Venezuela Redalyc [31] 2019 Turquía Scielo [32] 2019 Camboya Scopus [33] 2019 Portugal Scopus [34] 2020 Brasil Dialnet [35] 2020 Brasil Scopus [36] 2020 Rumania Scopus [37] 2021 Colombia Dialnet [38] 2021 España Ebsco [39] 2021 Brasil Ebsco [40] 2021 España Ebsco [41] 2021 España Proquest [42] 2021 Rumania Proquest [43] 2021 Indonesia Proquest [44] 2021 Brasil Scielo [45] 2021 Brasil Scielo [46] 2021 Brasil Scielo [47] 2021 Eslovaquia Scopus [48] 2021 India Scopus …”
Section: A Proceso De Recolección De Datosunclassified